2016
DOI: 10.1002/ece3.2469
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of methane from northern peatlands: a review of management impacts and implications for future management options

Abstract: Northern peatlands constitute a significant source of atmospheric methane (CH 4). However, management of undisturbed peatlands, as well as the restoration of disturbed peatlands, will alter the exchange of CH 4 with the atmosphere. The aim of this systematic review and meta‐analysis was to collate and analyze published studies to improve our understanding of the factors that control CH 4 emissions and the impacts of management on the gas flux from northern (latitude 40° to 70°N) peatlands. The analysis include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
168
4
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(189 citation statements)
references
References 195 publications
(217 reference statements)
15
168
4
2
Order By: Relevance
“…Our annual NEE‐CH 4 over the natural forest is similar to emissions from northern bogs (average = 9.5 g m −2 year −1 ) and around two times lower than CH 4 emissions from northern fens (average = 20.5 g m −2 year −1 ; Abdalla et al, ). Higher temperatures in tropical peatlands favor greater humification, selective removal of reactive labile carbohydrates, and accumulation of aromatic content leading to a highly recalcitrant residual peat (Brady, ; Hodgkins et al, ).…”
Section: Discussionsupporting
confidence: 60%
“…Our annual NEE‐CH 4 over the natural forest is similar to emissions from northern bogs (average = 9.5 g m −2 year −1 ) and around two times lower than CH 4 emissions from northern fens (average = 20.5 g m −2 year −1 ; Abdalla et al, ). Higher temperatures in tropical peatlands favor greater humification, selective removal of reactive labile carbohydrates, and accumulation of aromatic content leading to a highly recalcitrant residual peat (Brady, ; Hodgkins et al, ).…”
Section: Discussionsupporting
confidence: 60%
“…Only Herbst et al (2013) reported an annual CH 4 flux from a restored wetland in Denmark that was lower than in this study (9 to 13 g CH 4 -C m −2 yr −1 ). Our annual CH 4 flux at 17 ± 1.0 g CH 4 -C m −2 yr −1 was comparable to an average natural temperate wetland CH 4 flux, which is typically around 15 g CH 4 -C m −2 yr −1 (Abdalla et al, 2016;Fortuniak et al, 2017;Nicolini et al, 2013;Turetsky et al, 2014). The CH 4 fluxes from a number of temperate and tropical pristine wetlands exceeded the CH 4 fluxes reported in this study, including emissions from marshes in the southwestern US (130 g CH 4 -C m −2 yr −1 ; Whiting and Chanton, 2001), tropical wetlands in Costa Rica (82 g CH 4 -C m −2 yr −1 ; Nahlik and Mitsch, 2010), marshes in the midwestern US (50 g CH 4 -C m −2 yr −1 , Koh et al, 2009), all three studies based on chamber measurements, and an ombrotrophic bog in New Zealand (29 and 21 g CH 4 -C m −2 yr −1 based on EC measurements; Goodrich et al, 2015).…”
Section: Ch 4 Exchange 441 Annual and Seasonal Ch 4 Budgetssupporting
confidence: 67%
“…Peatlands are the most widespread of all wetland types in the world, representing 50 to 70 % of global wetlands (Roulet, 2000;Yu et al, 2010). Peatlands around the world sequester around 50 g CO 2 -C m −2 yr −1 Christensen et al, 2012;Humphreys et al, 2014;McVeigh et al, 2014;Peichl et al, 2014;Pelletier et al, 2015) and emit around 12 g CH 4 -C m −2 yr −1 (Abdalla et al, 2016;Brown et al, 2014;Jackowicz-Korczynski et al, 2010;Lai et al, 2014;Urbanová et al, 2013). Furthermore, it has been shown that it is crucial to include peatlands in the modelling and analysis of the global C cycle (Frolking et al, 2013;Kleinen et al, 2010;Wania et al, 2009).…”
mentioning
confidence: 99%
“…Similar to other studies, we observed, the main or combined effects of WT position (Moore & Knowles, 1989;Turetsky et al, 2008), peat temperature (Moore et al, 2011;Turetsky et al, 2008), and vegetation cover (Abdalla et al, 2016;Bubier et al, 1995;Moore et al, 2011) as controls on CH 4 fluxes. In contrast, the fen exhibited minimal impacts of the road on CH 4 fluxes.…”
Section: Discussionsupporting
confidence: 91%